Power Relation Between Katniss Everdeen and President Snow in The Hunger Games Trilogy - Shintya Princesa; Achmad Munjid (Universitas Gadjah Mada, 2023)
This paper aims to find out about the dynamic of the power relation between Katniss Everdeen and President Snow from The Hunger Games trilogy, and how the power relation reflects domination and resistance. For the analysis, this paper applies Foucault's theory of power relations. The discussion concludes that the power relation between Katniss and President Snow is formed through the distribution of power that makes them subjects who can exercise power, and in the process, leads them to create a power relation where they complement each other’s power. A productive network is then formed as they work out the power relation with objectives and rationalization to exercise their power throughout the trilogy. Furthermore, the domination and resistance are reflected in the power relation through the use of those two effects of power as strategies by President Snow and Katniss respectively. Resulting in interchanging responses of domination and resistance that affect a series of events in the story.